KEPUASAN PASIEN TERHADAP PELAYANAN FARMASI DI KLINIK NADYA MEDICHAL CENTER - Niko Prasetya; Leonov Rianto Rianto; Audia Tri Sonia (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2023)
Pharmaceutical services are one of the most important aspects in health care at the Nadya Medical Center clinic. The better level of pharmaceutical sevices will affect the level of patient satisfaction. Patients feel satisfied if the health services provided their expected. To measure patient satisfaction as an effort to improve service quality, patient satisfaction can be measured using the SERVQUAL (SERVICE QUALITY) method by making a comprehensive customer satisfaction assessment survey for services that prioritize pharmaceutical services. Customer satisfaction analysis is carried out based on five dimensions of service quality, namely responsiveness, reliability, assurance, empathy, and tangible. From these data, researchers want to know the effect of patient satisfaction on pharmaceutical services at the Nadya Medical Center Clinic. This study aims to determine the description of patient satisfaction with pharmaceutical services at the Nadya Medical Center clinic. This study uses quantitative descriptive research methods. This type of research is non-experimental research which is a type of research to find out an overview of the population and sample. From the average population for one month, namely 1,500 patients, and the samples was 306 patients as respondents. The sample in this study were patients at the Nadya Medical Center clinic. Data collection in this study used primary data in the form of a questionnaire. Based on the results of the research, respondents' assessment of all the largest dimensions was very satisfied with 156 respondents (51%), respondents' assessment of the largest reliability dimension was very satisfied 152 respondents (50%), respondents' assessment of responsiveness dimension was very satisfied 148 respondents (48%), respondents' assessment of the largest assurance dimension is satisfied 148 respondents (48%), respondents' assessment of the largest empathy dimension is satisfied 147 respondents (48%), respondents' assessment of the largest physical evidence dimension is very satisfied 145 respondents (47%). So that conclusion is patient satisfaction with pharmaceutical services at the Nadya clinic stated that they were very satisfied as many as 156 respondets (51%).